Comprehensive optimal photovoltaic inverter control strategy in unbalanced three-phase four-wire low voltage distribution networks - Su, Xiangjing; Masoum, Mohammad A.S; Wolfs, Peter (IET generation, transmission & distribution, 2014)
The continuous expansion of consumer-driven installations of residential rooftop photovoltaic (PV) systems causes serious power quality, notable voltage variations and unbalance, which limit the number and capacity of the further connections. The latent reactive power capability of PV inverters can increase the network PV hosting capability. This study proposes both reactive power control and real power curtailment as a comprehensive inverter control strategy to improve the operating performance of unbalanced three-phase four-wire low voltage distribution networks with high penetrations of residential PV systems. A multi-objective optimal power flow (OPF) problem that can simultaneously improve voltage magnitude and balance profiles while minimising network loss and generation costs is defined. The solution is found using the global solver based on Sequential Quadratic Programming algorithm with multiple starting points in Matlab. Detailed simulations are performed and analysed for typical operating scenarios over 24-h period on a real three-phase four-wire unbalanced distribution network in Perth Solar City trial, Australia. Smart meter readings are used to justify the accuracy and validation of the network model and the proposed multi-objective OPF model.